Kiḻakkē maṟainta katiravaṉ : Robert de Nobili, S.J. - Iṉṉāci, C., 1934- (Jeyakumāri Sṭōrs, 1980)
On the life and religious activism of Robert de' Nobili, 1577-1656, Catholic missionary and Tamil scholar.